Review on Sources and Handling Method of Pesticide Residues in Animal Products - Indraningsih . (Indonesian Center for Animal Research and Development, 2006)
Field studies and literature search showed that some pesticide residues either organochlorines (OC) or organophosphates (OP) were detected in animal products (meat and milk) . Pesticide residues in meat collected from West Java were detected at the level of 0 .8 ppb lindane and 62 ppb diazinon . While in meat from Lampung was detected at the level of 7 ppb lindane . 2 .7 heptachlor, 0 .8 endosulfan and 0 .5 ppb aldrin . Furthermore, pesticide residues were also detected in the milk collected from West, Central and East Java . The levels of lindane were 2,3 ; 15,9 ; 0,2 ppb ; heptachlor 8 ; 0 .4 and 0,05 ppb; diazinon 8 ; 0 and 1,8 ppb; CPM 0,4 ; 0,8 and 0 ppb ; endosulfan 0,1 ; 0,04 and 0,05 ppb for West, Central and East Java, respectively . The source of pesticide contamination in animal products is generally originated from feed materials, fodders . contaminated soils and water around the farm areas . Minimalization approach of pesticide residues in animal products could be conducted integratedly, such as through chemical process, biodegradation using microorganisms . Organic farming system is recognised as an alternative that may be applied to minimise contamination on agricultural land, eventually reducing pesticide residues in the agricultural products . Feeding with organic agricultural by-products with low pesticide residues appears to reduce pesticide residues in animal products . In order to eliminate pesticide contamination in soil, it has to be conducted progressively by implementing sustainable organic farming . Key words : Pesticide residues, meat, milk